EFEKTIVITAS ANALISIS AKAR MASALAH “METODE PEMBELAJARAN” PADA RAPOR PENDIDIKAN SEKOLAH DASAR PENGGERAK ANGKATAN I - Jannah, Ukhti Raudhatul; Basori, Indrianto Setyo; Amiruddin, Mohammad; Rifanda, Akhmad Riski; Dwi Agustin, Sisca Patricia (Balai Besar Guru Penggerak Jawa Timur, 2023)
The objectives of this research are (a) to analyze the effectiveness of the root of the problem related to learning methods in the education report card at the First Generation Pengpeng Elementary School, (b) to analyze the impact of this problem on the learning process and achievement of student learning outcomes, (c) to prepare recommendations and improvement strategies to address identified problems. The research method that will be used in this research is qualitative research which involves various approaches, such as classroom observations, interviews with teachers and students, as well as document studies (document analysis) related to the learning methods applied. The research subjects were 90 students with 18 students in grades 1-6 in each school, 5 principals, and 2 elementary school teachers for Class I (SDN Pandian I, SDN Patian II, SDN Bataal Barat I, SDN Banbaru I, SDN Sapeken IV). The results of this research are (a) the results of priority recommendations in education report cards carried out by schools (Education units) are very effective in overcoming the root of the problem of